Tartufo (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
Tartufo was the first public performance by students of the Artistic Education – Qualification in Performing Arts course. The first class of this course debuted with this text by Molière, directed by José Ronaldo Faleiro, at Teatro Álvaro de Carvalho, Florianópolis, on December 21, 1989. Editora-Chief and Editoras/Editor Associadas/o da Urdimento decided that to celebrate Urdimento's 25th anniversary, it was also important to remember and honor the founding foundations of the Performing Arts course at UDESC, which is why the exhibition of images, in this Photographic Essay, of the first public work of the first graduates in our Performing Arts course .
Keywords: photographic essay